Perlindungan Hukum Bagi Pekerja Rumah Tangga yang Menjadi Korban Kekerasan oleh Majikannya di Indonesia - Dwi Syafi'i, Azhari; Yayi Tarina, Dwi Desi; Hendrawin, Rasendriya; Febrian, Matthew (IAI Nasional Laa Roiba Bogor, 2024)
Domestic workers (DWs) or domestic assistants (ARTs) are a common occupation in Indonesia, with around 5 million people working as DWs by 2022. However, legal protection for domestic workers who are abused by their employers remains a complex issue. This study aims to identify the legal protections available for domestic workers who are victims of abuse in Indonesia. Although Law No. 13/2003 on Manpower recognizes domestic workers as workers, legal protection for them is limited as they are not considered workers in certain businesses. Minister of Manpower Regulation No. 2/2015 on the Protection of Domestic Workers is an attempt to provide protection, but still has weaknesses in covering aspects such as wage standards, working hours, and leave. In addition, the Criminal Code also provides protection against violence against domestic workers, but has limitations in terms of complaint offense. Legal protection for domestic workers who are victims of violence by their employers is hampered by the limited definition of employment relationship in the Manpower Law. Despite efforts through special regulations and criminal law, further efforts are needed to improve legal protection for domestic workers, including improving the definition of employment relationships, improving the implementation of ILO Conventions, and adjusting criminal law to more effectively address cases of violence against domestic workers.